Effect of diet on postprandial glycemic and insulin responses in healthy dogs - Vastolo, Alessandro; Gizzarelli, Manuela; Ruggiero, Alessio; Alterisio, Maria Chiara; Calabrò, Serena; Ferrara, Maria; Cutrignelli, Monica Isabella (Frontiers in Veterinary Science, 2023)
Introduction Dog owners have gradually changed their approach, paying more attention to the nutrition and health of their animals. Various pet foods with different ingredients and nutritional characteristics are available on the market. The present study aimed to evaluate the administration of three diets, namely, two grain-free (GF1 and GF2) and one grain-based (CB), with different sources of carbohydrates that can influence the glycemic and insulin postprandial responses in healthy dogs. Materials Fifteen healthy dogs were dived in three groups and alternatively fed each diet for 50 days. Blood samples were collected at beginning of each feeding period. Glycemia and insulin were measured before and after 120, 240 and 360 minutes diet administration to evaluate postprandial responses. Results GF2 diet showed the highest level of albumin and mean insulin concentration (p < 0.001). Furthermore, the GF1 diet caused the smallest (p < 0.001) glucose and insulin area under the curve (AUC) and the lowest (p < 0.05) glucose nadir. Otherwise, GF1 showed the highest (p < 0.01) insulin time to peak. The GF2 diet showed the highest level of albumin while reporting the lowest amount of fructosamine (p < 0.05). The diet GF2 registered the highest (p < 0.001) level of insulin zenith. The cereal-based (CB) diet reported the highest amount of fructosamine (p < 0.05). The CB diet had the highest levels of glucose and the highest (p < 0.001) glucose and insulin mean concentrations. Diet CB reported the lowest (p < 0.001) insulin nadir. Discussion Diets with different carbohydrate sources and chemical compositions could modulate the glycemic response in healthy dogs. Bearing in mind that glycemic/insulin postprandial responses influence energy availability and that different dogs have specific lifestyles, it may be preferable to also consider these aspects when choosing a maintenance diet for animals